Investigating mobile money acceptance in Somalia: An empirical study - Osman Sayid; Abdelghani Echchabi; Hassanuddeen Abd. Aziz Abdelghani Echchabi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The main purpose of this paper is to study the perception and willingness of Somali customers to adopt mobile money, based on an upgraded version of technology acceptance model. The questionnaire used in this study was distributed to 100 Somali customers, and the data gathered were then analysed using multiple regression and one sample t-test. The results indicate that perceived ease of use has a significant positive influence on the perceived usefulness of mobile money. Moreover, perceived usefulness and security were found to have a significant positive influence on attitude. Finally, social influence together with perceived usefulness both have significant positive influence on the Somali customers' intention to adopt mobile money. This is one of the first studies to be conducted on mobile money in Somalia, the study uses an upgraded version of technology acceptance model and it reports significant findings based on this approach.
Keywords: 330; Somalia; Mobile money; Multiple regression; TAM; Elektronisches Geld; Mobile Business; Finanzdienstleistung; Konsumentenverhalten; Somalia